A novel deletion upstream of POU3F4 in a Chinese family with X-linked deafness 2 and a literature review - Yang, Yanting; Huang, Shengwen; Liu, Yao; Mu, Dan; Bai, Ting; Jing, Xiaosha; Xing, Lingling; Liu, Hongqian (Frontiers in Genetics, 2025)
BackgroundX-linked deafness 2 (DFNX2) is a rare hereditary hearing loss characterized by progressive conductive and sensorineural hearing loss and a pathognomonic temporal bone deformity. DFNX2 is caused by mutations in the coding sequence or deletions upstream of POU3F4. Only 12 upstream deletions of POU3F4 associated with DFNX2 have been reported, and the precise mechanisms underlying its pathogenesis remain fully elucidated.MethodsWhole-genome Sequencing (WGS) and linkage analysis were performed to identify potential genetic etiologies. Gap-PCR and Sanger sequencing were used to validate candidate pathogenic variants and elucidate the breakpoints. Quantitative Polymerase Chain Reaction (qPCR) was conducted to evaluate the altered expression of both POU3F4 and its downstream target genes.ResultsHere, we identified a novel deletion approximately 795.5 kb in length, located about 140 kb upstream of POU3F4 in a large Chinese family. All patients are hemizygous for this deletion, and the breakpoints have been confirmed to be located at GRCh37(chrX): g.81840743_82636209. Additionally, qPCR analysis demonstrated a significant reduction in the expression levels of both POU3F4 and its downstream target genes in the affected patients, which had not been reported in previous studies. We expand the spectrum of pathogenic deletions upstream of POU3F4 associated with DFNX2.ConclusionThis study provides new molecular evidence that deletions upstream of POU3F4 can disrupt the expression of POU3F4 and its downstream target genes in humans. Our results also enhance the understanding of the pathogenic mechanisms underlying DFNX2 associated with these deletions, as well as the downstream gene networks of POU3F4.